Method for preparing degradable magnesium alloy intravascular stent through laser powder bed melting
By rationally designing the magnesium alloy composition and controlling the laser powder bed melting process and optimizing the surface treatment technology, a magnesium alloy vascular stent with excellent mechanical properties and controllable degradation rate was prepared, which solved the problems of insufficient mechanical properties and excessive degradation rate of magnesium alloy vascular stents in the prior art, and improved the biocompatibility and stability of the stent.
Patent Information
- Application Number
- CN202510307867.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The existing magnesium alloy vascular stents still lack reliable data support in terms of mechanical properties, degradation rate and biocompatibility, and the magnesium alloy stent prepared by laser powder bed melting has the problem of excessive degradation rate and insufficient mechanical strength.
By rationally designing the composition of magnesium alloy, controlling the process parameters during laser printing, and optimizing surface treatment technology, a magnesium alloy vascular stent with excellent mechanical properties and controllable degradation rate was prepared. Specific steps include preparing magnesium alloy powder, designing the bracket structure, laser powder bed melting and surface treatment.
The excellent mechanical properties, controllable degradation rate and good biocompatibility of magnesium alloy vascular stents are achieved, and the problems of insufficient mechanical properties and excessive degradation rate in traditional methods are solved, thereby improving the stability and biocompatibility of the stent.
Smart Images

Figure CN119819946A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing, and in particular relates to a method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting. Background Art
[0002] Vascular stents are used as an effective treatment for cardiovascular diseases such as coronary heart disease and hypertension. The main materials of traditional vascular stents are metal materials such as stainless steel and cobalt alloys. These materials have high mechanical strength, but long-term presence in the body may cause complications such as thrombosis, restenosis in the stent, chronic inflammatory response inside and outside the stent, etc. In order to reduce these problems, in recent years, degradable metal materials, especially magnesium alloys, have gradually become the research focus of vascular stent materials. Magnesium alloy materials have excellent biocompatibility, degradability and good mechanical properties. Especially in the interaction with human tissues, the degradation process of magnesium can effectively reduce the adverse reactions that may be caused by the long-term presence of metal stents in the body; however, the degradation rate of magnesium alloy materials in the body is relatively fast, which limits its application in vascular stents. In order to balance the degradation rate and mechanical properties, researchers have conducted extensive explorations in the composition, microstructure and surface treatment of magnesium alloys, and proposed a variety of methods, but these methods still have many shortcomings in practical applications.
[0003] Laser powder bed melting (LPBF) technology, as an additive manufacturing process, has shown broad application prospects in the medical field. By precisely controlling the heat energy input of the laser beam, the technology can melt metal powder layer by layer on the metal powder bed, and finally obtain a three-dimensional structure with complex geometric shapes. Compared with traditional processing methods, LPBF has the following significant advantages: High-precision manufacturing: LPBF technology can achieve micron-level processing accuracy, can accurately control the microstructure and porosity of the stent, and meet the strict requirements of vascular stents for dimensional accuracy and mechanical properties; High material utilization rate: Due to the use of powder materials, unmelted powder can be recycled and reused, with less material waste and relatively low cost; Complex structures can be manufactured: LPBF technology can manufacture complex geometric structures, such as porous, gradient pores, internal channels, etc. These structures are of great significance in improving the biocompatibility of vascular stents, promoting the growth of vascular endothelial cells, and reducing complications. Therefore, laser powder bed melting technology has great application potential in the preparation of magnesium alloy vascular stents, and can effectively solve the complex structure and performance optimization problems that are difficult to achieve with traditional manufacturing methods.
[0004] In the early days, magnesium alloy materials were not widely used in the field of vascular stents due to their high degradation rate and low mechanical strength. In the prior art, the mechanical properties and biocompatibility of magnesium alloys were gradually improved by adjusting the composition, microstructure and surface treatment method of magnesium alloys. For example, the addition of zinc, calcium, rare earth elements, etc. can improve the mechanical properties and corrosion behavior of magnesium alloys; surface coatings (such as polymer coatings, phosphating coatings, etc.) can effectively control the degradation rate and improve the stability of vascular stents, such as patent applications CN108014379A, CN104189963A, CN114904052A, CN116370709A, CN103418035A, international patents WO2023151343 (A1), WO2015172664 (A1) and EU patent EP3144018 (A4). At present, the main method for manufacturing magnesium alloy vascular stents is to first prepare magnesium alloy microtubes, then laser cut and laser engrave the microtubes, and use the high energy density of the laser to cut and engrave the magnesium alloy material to finally obtain a mesh of thin tubes, such as patent applications CN109433841A, CN105964716A and CN101249286A. However, the vascular stents obtained by this method have oxide layers and thermally damaged areas, which may make the surface quality uneven and prone to local overheating or ablation, resulting in problems such as unsatisfactory surface quality and low yield. In contrast, additive manufacturing technology provides higher flexibility and manufacturing precision. Patent applications such as CN 101856723A and CN106620837A disclose a molding method for preparing magnesium alloy vascular stents using additive manufacturing technology. Despite this, the biodegradable magnesium alloy vascular stents prepared by existing additive manufacturing technology still lack reliable data support in terms of mechanical properties, degradation rate and biocompatibility; currently, the laser powder bed melting method for preparing magnesium alloy stents still faces the problem of too fast degradation rate, which may cause the stent to fail prematurely and be unable to effectively support blood vessels; at the same time, there is also the problem of insufficient mechanical strength, which cannot meet the high strength requirements required for vascular stents. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting, aiming to solve the problems raised in the above-mentioned background technology.
[0006] The embodiment of the present invention is implemented as follows: a method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting, comprising the following steps: Preparation of magnesium alloy powder: weighing raw materials according to the following mass percentages: Sr 1-3%, Zr 0.5-1.5%, Bi 0.2-1%, Si 0.5-2%, Ti 0.1-0.5%, and the balance Mg, smelting to form a uniform liquid alloy, then spraying the liquid alloy with high-pressure argon gas, cooling it to form powder particles, and screening to obtain magnesium alloy powder; Stent structure design: Design the stent wall thickness and pore structure according to the size of the blood vessel and blood flow characteristics; Laser powder bed melting: magnesium alloy powder is laid on a substrate, the laser scanning path is designed according to the structure of the bracket, and interlayer scanning is used to prepare the magnesium alloy bracket; Surface treatment: The magnesium alloy stent is polished, cleaned and dried, then fluorinated, and then cleaned and dried.
[0007] Preferably, in the step of preparing the magnesium alloy powder, the smelting temperature is 700-750° C., and the particle size of the magnesium alloy powder obtained by screening is 30-60 μm.
[0008] Preferably, in the step of designing the support structure, the porosity of the support is 80-90%, and the wall thickness of the support is 0.3-0.5 mm.
[0009] Preferably, in the step of laser powder bed melting, the magnesium alloy powder is laid on the substrate with a thickness of 30-50 μm.
[0010] Preferably, in the step of laser powder bed melting, the interlayer scanning is specifically a method of rotating 67° for each printed layer, and the layer thickness is 20-30 μm.
[0011] Preferably, in the step of laser powder bed melting, the heating temperature of the substrate is 400-450°C.
[0012] Preferably, the parameters of the laser powder bed melting are: laser power 50-100 W, scanning speed 200-600 mm / s, scanning spacing 80-100 μm; The parameters of the outer contour are: laser power 40-50 W, scanning speed 400-600 mm / s.
[0013] Preferably, in the step of surface treatment, the polishing treatment is specifically to polish the magnesium alloy stent with a phosphoric acid solution for 300-350 seconds.
[0014] Preferably, in the step of surface treatment, the fluorination treatment is specifically as follows: immersing the magnesium alloy stent in hydrofluoric acid for 12-24 h, and shaking it with a shaker to make the fluorination uniform, forming a layer of MgF2 film on the surface of the magnesium alloy stent, and then placing it in a supersaturated hydroxyapatite solution, and shaking it with a shaker for 24-48 h.
[0015] Another object of an embodiment of the present invention is to provide a degradable magnesium alloy vascular stent, which is prepared by the above method.
[0016] A method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting provided in an embodiment of the present invention obtains excellent mechanical properties and an ideal controllable degradation rate by rationally designing alloy composition, controlling process parameters during laser printing, and optimizing surface treatment technology. This method can successfully prepare a vascular stent with good biodegradability without affecting the biocompatibility and mechanical strength of the magnesium alloy material. The porosity and structural morphology of the stent are precisely controlled by the laser powder bed melting process, thereby further improving the compressive strength, degradability and biocompatibility of the stent. Compared with traditional stent preparation methods, the stent prepared in an embodiment of the present invention can stably degrade in vivo, while having little stimulation to the inner wall of the blood vessel, reducing the risk of inflammatory response and foreign body rejection, thereby improving the clinical application effect after implantation. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A design drawing of a magnesium alloy vascular stent provided in Example 1 of the present invention; Figure 2 This is a morphology diagram of the degradable magnesium alloy vascular stent prepared in Example 1 of the present invention; Figure 3 The mechanical properties of the degradable magnesium alloy vascular stent prepared in Example 3 of the present invention are shown in FIG. Figure 4 The corrosion resistance results of the degradable magnesium alloy vascular stent prepared in Example 3 of the present invention are shown.
[0018] Figure 5 The cell survival rate result of the degradable magnesium alloy vascular stent prepared in Example 3 of the present invention; Figure 6 This is the hemolysis rate result of the degradable magnesium alloy vascular stent prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0020] A method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting, comprising the following steps: The first step is to prepare magnesium alloy powder: magnesium alloy is composed of magnesium, strontium, zirconium, bismuth, silicon and titanium elements, and its composition is calculated by mass percentage (Wt / %): strontium (Sr) 1-3, zirconium (Zr) 0.5-1.5, bismuth (Bi) 0.2-1, silicon (Si) 0.5-2, titanium (Ti) 0.1-0.5, and magnesium (Mg) is the balance. The purity of the metal magnesium, strontium, zirconium, bismuth, silicon and titanium used is greater than 99.99%; put it into an electric furnace for smelting, and the smelting temperature is generally controlled at 700-750 ° C. At this temperature, the alloy components will be fully dissolved and form a uniform liquid alloy. During the smelting process, an appropriate amount of degassing agent is added to remove gas impurities in the solution, and furnace gas protection is used to prevent the alloy from reacting with oxygen in the air; then use high-pressure argon gas to spray the liquid alloy, quickly cool it to form fine powder particles, and screen out magnesium alloy powder with a particle size range of 30-60 μm; Step 2: Stent structure design: The design of the stent should conform to the anatomical characteristics of human blood vessels to ensure that it can be correctly positioned in the blood vessels and has sufficient mechanical support. The wall thickness and pore structure of the stent should be designed according to the size of the blood vessels and blood flow characteristics. The wall thickness should be 0.3-0.5 mm and the porosity should be between 80-90% to promote blood circulation and provide sufficient biodegradation space. The angle between the support unit and the axial direction should not be greater than 45°. The third step is laser powder bed melting: the prepared magnesium alloy powder is evenly laid on the substrate to ensure the uniformity of the magnesium alloy layer, and the thickness is controlled at 30-50 μm. The laser scanning path is designed according to the structure of the bracket, and the interlayer scanning is carried out by rotating 67° for each printed layer. The layer thickness is 20-30 μm to ensure the uniform melting and density of the material. Ultra-high purity argon gas is used for protection during the laser powder bed melting process, and the substrate heating temperature is maintained at 400-450 ℃; the laser powder bed melting process parameters are: laser power 50-100 w, scanning speed 200-600 mm / s, scanning spacing 80-100 μm; in addition, the outer contour is scanned once with a laser power of 40-50 w and a scanning speed of 400-600 mm / s to further improve the printing quality and accuracy; Step 4: Surface treatment: The magnesium alloy stent is polished with a 5% phosphoric acid solution for 300 seconds. The polished stent is then thoroughly shaken and cleaned in anhydrous ethanol and then placed in a drying oven for thorough drying. The magnesium alloy stent is then immersed in 35% hydrofluoric acid for 12-24 hours and shaken on a shaker to ensure uniform fluorination, forming a layer of MgF2 film on the surface of the stent. The stent is then placed in a supersaturated hydroxyapatite solution and shaken on a shaker for 24-48 hours. It is then washed with deionized water and anhydrous ethanol and dried. The surface treatment enhances the corrosion resistance and biocompatibility of the stent, slows down the degradation rate of the magnesium alloy, and ensures the quality and function of the final stent.
[0021] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0022] Example 1: A method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting, comprising the following steps: The first step is to prepare magnesium alloy powder: the magnesium alloy composition is calculated by weight percentage (Wt / %): 1 strontium (Sr), 0.5 zirconium (Zr), 1 bismuth (Bi), 0.5 silicon (Si), 0.5 titanium (Ti), and the balance of magnesium (Mg). It is placed in an electric furnace for smelting, and the smelting temperature is controlled at 700-750 ° C. Then, high-pressure argon gas is used to spray the liquid alloy, and it is quickly cooled to form fine powder particles, and the magnesium alloy powder with a particle size range of 30-60 μm is screened out; Step 2: Design of the support structure: The wall thickness of the support is 0.5 mm, the porosity is 85%, and the angle between the support unit and the axial direction is no more than 45°. Figure 1 As shown; Step 3: Laser powder bed melting: The prepared magnesium alloy powder is evenly laid on the substrate with a thickness of 30-50 μm. The laser scanning path is designed according to the structure of the bracket. The interlayer scanning is performed by rotating 67° for each printed layer with a layer thickness of 30 μm. Ultra-high purity argon gas is used for protection during the laser powder bed melting process, and the substrate heating temperature is maintained at 420°C. The laser powder bed melting process parameters are: laser power 60 W, scanning speed 200 mm / s, scanning spacing 80 μm; in addition, the outer contour is scanned once with a laser power of 40 W and a scanning speed of 400 mm / s. Step 4: Surface treatment: The magnesium alloy stent was polished with a 5% phosphoric acid solution for 300 seconds. The polished stent was then fully shaken and cleaned in anhydrous ethanol and then placed in a drying oven for full drying. The magnesium alloy stent was then immersed in 35% hydrofluoric acid for 15 hours and shaken on a shaker to ensure uniform fluorination, so that a layer of MgF2 film was formed on the surface of the stent. The stent was then placed in a supersaturated hydroxyapatite solution and shaken on a shaker for 48 hours. It was then washed with deionized water and anhydrous ethanol and dried to obtain a degradable magnesium alloy vascular stent. Its morphology is as follows: Figure 2 shown.
[0023] Example 2: Compared with Example 1, the only difference is that the magnesium alloy composition, by mass percentage (Wt / %), is strontium (Sr) 2, zirconium (Zr) 0.5, bismuth (Bi) 1, silicon (Si) 1, titanium (Ti) 0.25, and the balance is magnesium (Mg). Other steps and parameters are the same as those in Example 1.
[0024] Example 3: Compared with Example 1, the only difference is that the magnesium alloy composition, by mass percentage (Wt / %), is 3 strontium (Sr), 1 zirconium (Zr), 0.5 bismuth (Bi), 2 silicon (Si), 0.1 titanium (Ti), and the balance is made up of magnesium (Mg). Other steps and parameters are the same as those in Example 1.
[0025] Example 4: Compared with Example 1, the only difference is that the magnesium alloy composition, by mass percentage (Wt / %), is 1 strontium (Sr), 1 zirconium (Zr), 0.5 bismuth (Bi), 0.5 silicon (Si), 0.5 titanium (Ti), and the balance is made up of magnesium (Mg). Other steps and parameters are the same as those in Example 1.
[0026] Example 5: Compared with Example 1, the only difference is that the magnesium alloy composition, by mass percentage (Wt / %), is strontium (Sr) 2, zirconium (Zr) 1.5, bismuth (Bi) 0.2, silicon (Si) 1, titanium (Ti) 0.25, and the balance is magnesium (Mg). Other steps and parameters are the same as those in Example 1.
[0027] Example 6: Compared with Example 1, the only difference is that the magnesium alloy composition, by mass percentage (Wt / %), is 3 strontium (Sr), 1.5 zirconium (Zr), 0.2 bismuth (Bi), 2 silicon (Si), 0.1 titanium (Ti), and the balance is made up of magnesium (Mg). Other steps and parameters are the same as those in Example 1.
[0028] Performance Test: The samples prepared in Example 3 were tested for mechanical properties, corrosion resistance and biocompatibility, and the tensile strength and elongation results were obtained as follows: Figure 3 As shown in the simulated blood environment, the degradation rate is Figure 4As shown, the cytotoxicity test results of Example 3 and the untreated vascular stent are compared. Figure 5 As shown, the hemolysis test results are compared with Figure 6 As shown; The samples prepared in other embodiments were tested respectively, and the results were summarized as shown in Table 1: Table 1 ; It can be seen from Table 1 that the samples prepared in the embodiments of the present invention have a tensile strength of 300-322 MPa and an elongation of 17-22.4%, have good mechanical properties, a degradation rate of 0.4-0.5 mm / y in a simulated blood environment, have good corrosion resistance, can be slowly degraded in the body, and have a cell survival rate of 96-99% after immersion for 7 days. The hemolysis rate is 2.8-3.2% after incubation in the blood at 37°C for 1 hour, and has excellent biocompatibility.
[0029] In summary, the method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting provided in the embodiment of the present invention is to obtain a vascular stent with excellent mechanical properties, controllable degradation rate and good biocompatibility by designing the composition of the magnesium alloy material, controlling the process parameters and surface treatment during the laser printing process, and solve the following problems: The problem of insufficient mechanical properties of magnesium alloy vascular stents. Conventional magnesium alloy vascular stents may have insufficient mechanical properties and cannot provide sufficient support, resulting in the possibility of rupture or excessive deformation of the vascular stent after implantation. The laser powder bed melting technology provided by the embodiment of the present invention can accurately control the alloy composition and microstructure of the magnesium alloy, optimize its mechanical properties, and ensure the stability and effectiveness of the stent after implantation. The problem of too fast or too slow degradation rate of magnesium alloy vascular stents. Too fast degradation will cause the stent to fail before the blood vessel is repaired, while too slow degradation may cause foreign body reaction or thrombosis in the blood vessel. The embodiment of the present invention uses laser powder bed melting technology to accurately control the microstructure of magnesium alloys, and optimizes the degradation rate through surface treatment to synchronize it with the blood vessel repair process, thereby avoiding the problem of too fast or too slow degradation; The surface of a magnesium alloy stent may have uneven roughness and corrosion, which may affect the bonding between the stent and the blood vessel wall, resulting in poor biocompatibility and even inducing immune response or inflammation. The embodiments of the present invention optimize the surface roughness of the stent and adopt appropriate post-processing processes to make the vascular stent facilitate the attachment and growth of the vascular endothelium, improve the bonding between the stent and the blood vessel wall, thereby enhancing its biocompatibility, reducing immune response and inflammatory response, and reducing the risk of secondary surgery.
[0030] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting, characterized in that: The following steps are involved: Preparation of magnesium alloy powder: weighing raw materials according to the following mass percentages: Sr 1-3%, Zr 0.5-1.5%, Bi 0.2-1%, Si 0.5-2%, Ti 0.1-0.5%, and the balance Mg, smelting to form a uniform liquid alloy, then spraying the liquid alloy with high-pressure argon gas, cooling it to form powder particles, and screening to obtain magnesium alloy powder; Stent structure design: Design the stent wall thickness and pore structure according to the size of the blood vessel and blood flow characteristics; Laser powder bed melting: magnesium alloy powder is laid on a substrate, the laser scanning path is designed according to the structure of the bracket, and interlayer scanning is used to prepare the magnesium alloy bracket; Surface treatment: The magnesium alloy stent is polished, cleaned and dried, then fluorinated, and then cleaned and dried.
2. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of preparing the magnesium alloy powder, the smelting temperature is 700-750° C., and the particle size of the magnesium alloy powder obtained by screening is 30-60 μm.
3. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of designing the support structure, the porosity of the support is 80-90%, and the wall thickness of the support is 0.3-0.5 mm.
4. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of laser powder bed melting, the magnesium alloy powder is laid on a substrate with a thickness of 30-50 μm.
5. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of laser powder bed melting, the interlayer scanning is specifically a method of rotating 67° for each printed layer, and the layer thickness is 20-30 μm.
6. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of laser powder bed melting, the heating temperature of the substrate is 400-450°C.
7. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: The parameters of the laser powder bed melting are: laser power 50-100 W, scanning speed 200-600 mm / s, scanning spacing 80-100 μm; The parameters of the outer contour are: laser power 40-50 W, scanning speed 400-600 mm / s.
8. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the step of surface treatment, the polishing treatment is specifically to polish the magnesium alloy stent with a phosphoric acid solution for 300-350 seconds.
9. The method for preparing a degradable magnesium alloy vascular stent by laser powder bed melting according to claim 1, characterized in that: In the surface treatment step, the fluorination treatment is specifically as follows: the magnesium alloy stent is immersed in hydrofluoric acid for 12-24 hours, and shaken with a shaker to make the fluorination uniform, forming a layer of MgF2 film on the surface of the magnesium alloy stent, and then placed in a supersaturated hydroxyapatite solution, and shaken with a shaker for 24-48 hours.
10. A degradable magnesium alloy vascular stent, characterized in that: It is prepared by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Degradable chemical bitter earth alloy bracket and method of preparing the same
CN101249286A
Selective laser melting (SLM) molding method for magnesium alloy stent
CN101856723A
Preparation method of surface coating capable of regulating degradation rate of magnesium alloy intravascular stent
CN103418035A
Preparation method of surface coating capable of lowering degradation rate of fully-degradable magnesium alloy vascular stent
CN104189963A
One-step forming processing method of magnesium alloy small-diameter thin-wall capillary tube used for vascular stent
CN105964716A